Selulosa Asetat dari Batang Singkong dengan Proses Cellanase - Yogi Irfan Maulana; Esa Wahyu Nur Hidayat; Mutasim Billah (G-Tech: Jurnal Teknologi Terapan, 2025)
Cassava stalks waste can be used as a material for making particleboard, crafts, briquettes, charcoal, bioethanol, and producing alpha-cellulose. Alpha-cellulose produced from cassava stems can be used as Cellulose Acetate. This study aims to obtain cellulose acetate from cassava stems and find relatively good conditions based on variations in acetylation time and volume of acetic anhydride. The process of making cellulose into cellulose acetate is carried out in several stages, namely pre-treatment, cellulose isolation, and acetylation. In the pre-treatment process, cassava stems will be reduced in size and softened to facilitate fiber extraction. Next, cellulose isolation is carried out by delignification and bleaching to obtain alpha-cellulose. In the acetylation stage, cellulose is first activated with glacial acetic acid before being acetylated with acetic anhydride. In this study, the effect of acetylation time (30, 60, 90, 120, 150 minutes) and the effect of adding volume (10, 12.5, 15, 17.5, 20 ml) on the acetyl content and degree of substitution of cellulose acetate from cassava stlaks were investigated. Based on the results of the study, the relatively good acetyl content and degree of substitution were obtained at a volume of 20 ml and a time of 150 minutes, with an acetyl content of 34.8% and a degree of substitution of 1.987. The synthesized cellulose is classified as monoacetate cellulose, which can be used in the manufacture of plastics and paints.